PENGARUH TARAF KONSENTRASI ATONIK DAN LAMA PERENDAMAN TERHADAP PERTUNASAN RIMPANG JAHE GAJAH ( Zingiber officinale Rose.) - Josina Irene Brigetha Hutubessy; Sukar Sukar; Karyoto Karyoto (Agriculture Faculty of Flores University, 2008)
This research intends to know the effect of the atonic concentration level in a soak of growing budding jahe Gajah rhizome. This research is experiment methods used to block multiple random designs and used atonic concentration 0,04%, 0,06%, 0,08% and soak duration 1 hours, 3 hours and 5 hours- The result of research indicated that 0,08% atonic concentration use and 3 hours soak duration caused time for budded better. No real effects of Atonic concentration on the amount of bud, the height of bud, length and amount of root.